2017
DOI: 10.1111/inm.12320
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of non‐pharmacological interventions attempted prior to pro re nata medication use

Abstract: The aim of the present study was to elucidate what non-pharmacological interventions are applied by nursing staff prior to the administration of psychotropic pro re nata (PRN) medication. Best practices would instruct clinical staff to provide non-pharmacological strategies, such as de-escalation and skills coaching, as the first response to patient distress, anxiety, or agitation. Non-pharmacological strategies might be safer for patients, promote more collaborative relationships, and facilitate greater skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 24 publications
(34 reference statements)
5
33
0
Order By: Relevance
“…In our own work, we found that nurses documented their use of non‐pharmacological strategies before giving psychotropic PRN medication in only 38% of PRN administrations (Martin et al . ). The reasons for not attempting non‐pharmacological interventions could be due to a variety of factors.…”
Section: Introductionmentioning
confidence: 97%
“…In our own work, we found that nurses documented their use of non‐pharmacological strategies before giving psychotropic PRN medication in only 38% of PRN administrations (Martin et al . ). The reasons for not attempting non‐pharmacological interventions could be due to a variety of factors.…”
Section: Introductionmentioning
confidence: 97%
“…Despite a lack of evidence, the average reported rate of PRN administration on adult inpatient psychiatric units is around 70-80%, ranging from 20% to 100% (Baker et al 2008). Common PRN medications used on adult units include antipsychotic medications (first and second generation), anxiolytics, and hypnotics, with benzodiazepines being the most frequently used (Martin et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are different perceptions and opinions amongst physicians that prescribe, and nurses that administer, PRN medication [4,55]. Additionally, there are controversies regarding the use of PRN medications and non-pharmacological strategies including counselling, distraction, verbal and non-verbal de-escalation, massage, and education [4,5,29,56,57]. The improvement of PRN prescription practice and promotion of PRN prescription and administration requires changes in the healthcare policies of patient safety in care homes [27,58,59], including the mandate of formalised, systematic checking of residents for potential ADRs [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…PRN is categorized as unscheduled medication administration either alone or in addition to routine/regular prescriptions [1]. It is frequently used for medications prescribed by physicians and administered based on nurses' judgements of patients' needs [2][3][4][5][6][7], but PRN medications are sometimes self-administered or given by family or informal caregivers [2]. PRN is commonly used to prescribe medications required in particular conditions, such as a complement to regularly scheduled medications [8].…”
Section: Introductionmentioning
confidence: 99%